The Influence of Service Quality, Information and Timeliness on Customer Satisfaction For Users of The Expedition PT. XYZ South Jakarta 2024 - Sonya Sidjabat; Rully Indrawan; Natasya De La Rosa; Nurhaliza Nurhaliza (Dinasti International Journal of Education Management and Social Science, 2026)
This study aims to improve our understanding of the factors affecting customer satisfaction with the PT. XYZ expedition service. Many people prefer to shop online rather than offline. This study is a quantitative descriptive study conducted by collecting data through questionnaires distributed to PT. XYZ service users. The analysis used is SEM-PLS (Structural Equation Model - Partial Least Squares). With a total of 110 respondents with criteria having used PT. XYZ for the last 6 months and domiciled in South Jakarta, taking a pure sample to collect data through a questionnaire using a Likert scale of 1-5. The results of this article are: 1) Service quality affects customer satisfaction; 2) Information affects customer satisfaction; 3) Timing affects customer satisfaction. In this study, the satisfaction rate of PT. XYZ customers in South Jakarta was 63.3%; the remaining 36.7% was due to other variables not discussed in this study.